Prevalence of Camel Mange and Associated Risk Factors in The Banadir Region, Somalia - Moktar Omar Sheikh Mohamed; Jeilani Buzuri Mio; Abdullahi Abdirashid Abdullahi; Ilyaas Abukar Adow; Mahad Abdinur Derow (Journal of Applied Veterinary Science And Technology, 2024)
Background: Camel mange, a highly infectious and itchy condition brought on by Sarcoptes scabiei var. cameli, can be spread through direct and indirect contact. It is one of the most significant parasitic diseases affecting camels, severely impacting their productivity and health, with substantial economic consequences. Purpose: Assessing the prevalence of camel mange mites and identifying potential risk factors.  Method:  This cross-sectional study was carried out between June 2023 and February 2024 in the Benadir region of Somalia. A total of 384 camels were randomly selected for skin scrapings, with samples from suspected lesions being microscopically examined. Results:  Of these, 82 camels (21%) were infested with mange mites, with Sarcoptes scabiei var. cameli identified as the only mite species. The research uncovered that the condition of the body, the size of the herd, and age substantially influenced the prevalence of mange mites (p<0.05), while district, sex, and age had no significant effect on infestation rate (p>0.05). Conclusion:  The results suggest that mange mite infestations in the camel populations in the Benadir region negatively affect their health and productivity. Therefore, there is an urgent need to improve management practices and conduct further research and control measures to mitigate the effects of mange mite infestations on camel husbandry.